ON THE MATHEMATICAL MODEL FOR THE SPREAD AND CONTROL OF MEASLES - Santali, Sule; Musa, Bawa; Agboluaje, Ayodele Abraham; Abubakar, Abdulkadir (FUDMA Journal of Sciences, 2025)
Measles is a highly contagious and potentially deadly disease that continues to pose a significant public health challenge, particularly in regions with suboptimal vaccination coverage. Measles remains a major threat to children, leading to severe complications and even death, despite the success of vaccination programs worldwide. This study delves into the dynamics of measles transmission and control, focusing on the development of a mathematical model. The research aims to propose a mathematical model using a system of first-order differential equations, categorizing the population into compartments representing vaccination(V), susceptible(S), exposed(E), infection(I), treatment(T) and recovery(R). The objectives include: obtaining Disease-Free Equilibrium State (DFES), performing stability analysis for DFES and the numerical simulation of the model was presented using maple software. Ultimately, the goal is to inform evidence-based strategies for measles vaccination and prevention, mitigating the disease’s impact on children’s health.